Niger : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Modification of Performance Criterion and Extension of Arrangement. (IMF Staff Country Reports; Country Report ;, 2004)
Niger's sociopolitical environment remains fragile, with a continuation in early 2003 of the social tensions that surfaced in 2002. In the wake of a satisfactory macroeconomic performance in 2002, activity has continued to be buoyant in all sectors of the economy, particularly in the construction and trade sectors, and together with the onset of a favorable rainy season, has supported the economic environment underlying the program for 2003. The broadly satisfactory track record of Niger in policy implementation has continued in 2003.